Palmolive Building, by night (Max Rigot Selling Co)
A spectacular night-time feature of the new Palmolive Building is the Lindberg Beacon. Mounted atop a shining bronze column, 603 feet above Chicago, its two billion candlepower beam is visible to aviators in the air as far east as Cleveland, Ohio, and as far south as St. Louis, Missouri. Government Surveyors have determined the location of thei Beacon as being Latitude, 41 53' 59 1/4"" N., Longitude 87 37' 25"" W.